Assessment of postoperative relief and complications correlated with septoplasty and septoplasty with turbinectomy - Rawat, Sharad; Mahajan, G. D.; Sonar, Tejal; Rathod, Ashwini (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Nasal obstruction was the common symptom of deviated nasal symptom. Many surgical procedures are available to correct the deviation. The current study was aimed to assess and compare the postoperative relief and complications of septoplasty alone and septoplasty with turbinectomy. Methods: This prospective study was done on 50 patients with nasal blockage due to deviated nasal septum. Study was done at department of ENT, Dr. D.Y. Patil Medical College and Hospital, DPU between July 2016 to September 2018. Patients randomly selected and operated with septoplasty alone (n=25) and septoplasty with turbinectomy (n=25). Assessment and comparisons was made in terms of postoperative relief and complications in both the groups. Results: Significant postoperative relief was seen in group of patients after septoplasty with turbinectomy. Retained deviation and dryness of nose are the common complications observed in group of patients treated with septoplasty and septoplasty with turbinectomy respectively and on follow up of 4 weeks postoperatively the rate of frequency of complications was reduced in group of patients managed with septoplasty with turbinectomy. Conclusions: Postoperative relief and reduction in complication rate after 4 week follow-up was higher in group of patients operated with septoplasty with turbinectomy compared to group of patients managed with septoplasty alone.